Od pedagogiki kolektywu do pedagogiki kolektywizującej. Idee wychowawcze Antona Makarenki w świetle filozofii i pedagogiki wspólnotowości - Karolina Starego (Problemy Wczesnej Edukacji)
The purpose of this paper is to highlight the continuing relevance of some elements of Anton Makarenko’s pedagogical thought. My other aim is to reinterpret those elements in the light of contemporary theories of commonality and communal education. The category that is reinterpreted in relation to the modern theories of the production of the common and the new forms of being together that thus produced, is Makarenko’s notion of the “collective”. Based upon this, I propose an idea of a collectivizing pedagogy, that is a remedy for the current neoliberal delegitimization of all forms of common identity, and the latter’s effects such as incapability of imagining (and consequently teaching about) the possibility of a communal, solidary action.